Is Export-Led Growth Hypothesis Exist in Saudi Arabia? Evidence from an ARDL Bounds Testing Approach - FAISAL, Faisal; TÜRSOY, Turgut; REŞATOĞLU, Nil GÜNSEL (Asian Journal of Economic Modelling, 2017)
The study investigates the relationship between economic growth, imports and export for Saudi Arabia by using the time series data from 1968-2014. The study employs the recently developed ARDL-bounds testing approach. The estimations of the ARDL-bounds testing approach indicated that imports, export and GDP are strongly co-integrated. The finding of the study further indicated that exports have positive impact on the economic growth in the long run. This specifies that if exports are increased by one percent the economic growth is increased by 3.39%, implying the validity of export-led growth hypothesis. The parameter of error correction term is 2.89% that represents the speed of adjustment. This implies that economic growth converges to its long run equilibrium position by 2.89% speed of adjustments via channel of imports and Exports. As the speed of adjustment is very low and it would take time to return back to the equilibrium level, that confirms the stability of the system. The reliability and validity of the estimations results are confirmed by the diagnostics tests both in short and long run. Finally, the results of the granger causality suggest, a uni-directional causality running from export to GDP, suggesting the validity of export led growth hypothesis. While another uni-directional causality has been found from imports to exports. Being the member of OPEC, Saudi Arabia exports mainly comprises of oil that exposes the economy of country to external shocks. The study suggested that Saudi Arabia needs to invest more in the non-oil sector and diversify their investment by attracting more FDI. This will cause the economic growth to increase and also be more flexible to any external shocks.